2013
DOI: 10.1159/000354785
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Attitudes toward Personalized Medicine

Abstract: Background/Aims: Patient concerns regarding personalized medicine may limit its use. This study assesses racial differences in attitudes toward personalized medicine, evaluating variables that may influence these attitudes. Methods: A convenience sample of 190 adults (≥18 years) from an academic primary care practice was surveyed regarding awareness and acceptance of personalized medicine, plus concerns and benefits regarding its use. Logistic regressions predicting awareness, acceptance and concerns were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…Indeed, the former were significantly more preoccupied about the potential negative impact of unfavorable test results on employment and insurability. Previous publications have mentioned these two issues as well, 8,10,11,14,[20][21][22][23][24][25]29,31,33,35,[39][40][41] but our study is the first to indicate that this concern is more prevalent in healthy individuals compared with patients with chronic diseases. Possible explanations for these intergroup differences include the fact that HF patients were older and more frequently retired and that many patients had already been denied insurance coverage due to their chronic illness.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Indeed, the former were significantly more preoccupied about the potential negative impact of unfavorable test results on employment and insurability. Previous publications have mentioned these two issues as well, 8,10,11,14,[20][21][22][23][24][25]29,31,33,35,[39][40][41] but our study is the first to indicate that this concern is more prevalent in healthy individuals compared with patients with chronic diseases. Possible explanations for these intergroup differences include the fact that HF patients were older and more frequently retired and that many patients had already been denied insurance coverage due to their chronic illness.…”
Section: Discussionmentioning
confidence: 53%
“…As in previous publications, 14,21,22,34,40,44 physicians and pharmacists were identified as the most appropriate health-care professionals to handle pharmacogenomic information. Fewer participants indicated that they would grant a similar access to genetic counselors, but this could be explained by the fact that only a minority was aware of the role and responsibilities of these professionals.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations